2019
DOI: 10.1109/tnnls.2018.2838039
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Real-Valued Time-Delay Neural Network for Compensation of Distortions and Impairments in Wireless Transmitters

Abstract: A digital predistorter, modeled by an augmented real-valued time-delay neural network (ARVTDNN), has been proposed and found suitable to mitigate the nonlinear distortions of the power amplifier (PA) along with modulator imperfections for a wideband direct-conversion transmitter. The input signal of the proposed ARVTDNN consists of Cartesian in-phase and quadrature phase (I/Q) components, as well as envelope-dependent terms. Theoretical analysis shows that the proposed model is able to produce a richer basis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
106
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(108 citation statements)
references
References 25 publications
0
106
0
2
Order By: Relevance
“…There is disagreement about whether the brain represents time on a linear (Gibbon, 1977 ; Gibbon and Church, 1981 ; Roberts, 1981 ; Church and Gibbon, 1982 ; Gallistel, 1999 ; Wearden and Jones, 2007 ) or logarithmic (Church and Deluty, 1977 ; Staddon and Higa, 1999 ; Roberts, 2006 ; Yi, 2009 ) scale. Some studies have reported linear changes in neural activity over time (e.g., Komura et al, 2001 ; Machens et al, 2010 ), but we showed that activity profiles of mPFC neurons are better described by logarithmic than linear functions in the current task (Kim et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is disagreement about whether the brain represents time on a linear (Gibbon, 1977 ; Gibbon and Church, 1981 ; Roberts, 1981 ; Church and Gibbon, 1982 ; Gallistel, 1999 ; Wearden and Jones, 2007 ) or logarithmic (Church and Deluty, 1977 ; Staddon and Higa, 1999 ; Roberts, 2006 ; Yi, 2009 ) scale. Some studies have reported linear changes in neural activity over time (e.g., Komura et al, 2001 ; Machens et al, 2010 ), but we showed that activity profiles of mPFC neurons are better described by logarithmic than linear functions in the current task (Kim et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Real-valued time-delay neural network (RVTDNN) [4] is a well-known model of the I/Q separation type. In particular, the augmented real-valued time-delay neural network (ARVTDNN) [5] works by adding envelope signals to the input signals. Moreover, reference [6] and [7] present methods for MIMO transmitters that compensate not only PA distortion but also cross talk.…”
Section: Introductionmentioning
confidence: 99%
“…The neural network models used for PA behavioral modeling mainly include bidirectional long short-term memory (BiLSTM) neural network [9], radial basis function (RBF) neural network [10] and time delay neural network (TDNN) [8]. However, there are few DPD models to jointly compensate I/Q imbalance and PA nonlinearities [11]- [13].…”
Section: Introductionmentioning
confidence: 99%